The global NAFLD policy review and preparedness index: Are countries ready to address this silent public health challenge? - YILMAZ, YUSUF (My University, 2021)
BACKGROUND & AIMS: Non-alcoholic fatty liver disease (NAFLD) is a highly prevalent, yet largely underappreciated liver condition which is closely associated with obesity and metabolic disease. Despite affecting an estimated 1 in 4 adults globally, NAFLD is largely absent on national and global health agendas. METHODS: We collected data from 102 countries, accounting for 86% of the world population, on NAFLD policies, guidelines, civil society engagement, clinical management, and epidemiologic data. A preparedness index was developed by coding questions into 6 domains (policies, guidelines, civil awareness, epidemiology and data, NAFLD detection, and NAFLD care management) and categorising the responses as high, medium, and low; a multiple correspondence analysis was then applied. RESULTS: The highest scoring countries were India (42.7) and the United Kingdom (40.0), with 32 countries (31%) scoring zero out of 100. For 5 of the domains a minority of countries were categorised as high-level while the majority were categorised as low-level. No country had a national or sub-national strategy for NAFLD and <2% of the different strategies for related conditions included any mention of NAFLD. National NAFLD clinical guidelines were present in only 32 countries. CONCLUSIONS: Although NAFLD is a pressing public health problem, no country was found to be well prepared to address it. There is a pressing need for strategies to address NAFLD at national and global levels. LAY SUMMARY: Around a third of the countries scored a zero on the NAFLD policy preparedness index, with no country scoring over 50/100. Although NAFLD is a pressing public health problem, a comprehensive public health response is lacking in all 102 countries. Policies and strategies to address NAFLD at the national and global levels are urgently needed.
Keywords: global public health; health policy; liver health; multiple correspondence analysis; Non-alcoholic fatty liver disease (NAFLD); non-alcoholic steatohepatitis (NASH); policy preparedness